1972
DOI: 10.1080/10862967209547062
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Factors Related to Change in Attitude toward Reading

Abstract: This article describes a study conducted to determine the relationship between change in attitude toward reading and (1) achievement in the basic word identification, vocabulary, and reading comprehension skills, (2) sex, (3) socioeconomic status, and (4) age. While the students in the experimental group made significantly greater gains than the students in the control group in both change in attitude toward reading and achievement in most of the skills tested, statistically significant relationships were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…To date studies which have attempted to explain leisure reading have in the main lacked an affective component. A number of studies have demonstrated that improvement in reading attitude is associated with higher levels of reading achievement (Healy, 1965; Roettger et al, 1979;Rowell, 1972;Walberg and Tsai, 1984), which, in turn, correlates with amount of leisure reading (Connor, 1954;Greaney, 1980;Long and Henderson, 1973;Maxwell, 1977;Whitehead et al, 1975). Thus, it would seem reasonable to include an attitudinal measure in a model of leisure reading.…”
Section: Introductionmentioning
confidence: 99%
“…To date studies which have attempted to explain leisure reading have in the main lacked an affective component. A number of studies have demonstrated that improvement in reading attitude is associated with higher levels of reading achievement (Healy, 1965; Roettger et al, 1979;Rowell, 1972;Walberg and Tsai, 1984), which, in turn, correlates with amount of leisure reading (Connor, 1954;Greaney, 1980;Long and Henderson, 1973;Maxwell, 1977;Whitehead et al, 1975). Thus, it would seem reasonable to include an attitudinal measure in a model of leisure reading.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the research in this area has examined attitudes toward reading, their development and their role in reading achievement. While the research on this latter question is inconsistent, many studies have found moderate relationships at various grade levels between reading achievement and attitudes (Askov & Fischbach, 1973;Bernstein, 1955;Groff, 1962;Nealeetal., 1970;Ransbury, 1973;Rowell, 1972;Schnayer, 1969).…”
Section: Introductionmentioning
confidence: 94%
“…Attitude changes affected the amount read and level of achievement and persisted into junior high school. Rowell (1972) developed a Likert type 5 point observation checklist, A Scale of Reading Attitude Based on Behavior, for use with elementary subjects. The scale is scored 1 to 5 for each of 16 items and summed for a total attitude score.…”
Section: Direct Observationmentioning
confidence: 99%